(untitled) (Latakia University Journal -Medical Sciences Series, 2023)
Suspensions are liquid pharmaceutical forms consisting of heterogeneous systems, in which the active substance is dispersed homogeneously in a liquid medium in which it shows poor solubility, as the formulation of suspensions is important for poorly soluble pharmaceutical substances in water that we want to administer to patients who suffer from difficulty swallowing solid pharmaceutical forms. Albendazole is one of the most effective anthelmintics, which also has proven anti-cancer activity, and it has poor water solubility. Therefore, Albendazole was prepared in the form of a pharmaceutical suspension, and the effect of xanthan gum and CMC Na as suspending agents on the flocculation of the suspension and its properties was investigated. The formulations containing xanthan gum at concentrations of 0.2, 0.25, and 0.3% as a suspending agent showed large sedimentation volume, easy resuspendability and obvious stability after storage for 4 months at room temperature, especially for a concentration of 0.3%, while the formulations containing CMC Na at a concentration of 1 %, the sedimentation volume was low and it was difficult to resuspend it. As for the formulas prepared at concentrations of 0.3 and 0.5% of CMC Na, it showed an acceptable sedimentation volume, but it had poor stability after storage.